Loneliness, social relationships, and mental health in adolescents during the COVID-19 pandemic - Cooper, K; Hards, E; Moltrecht, B; Reynolds, S; Shum, A; McElroy, E; Loades, M (Elsevier, 2021)
Loneliness is a common experience in adolescence and is related to a range of mental health problems. Such feelings may have been increased by social distancing measures introduced during the COVID-19 pandemic. We aimed to investigate the effect of loneliness, social contact, and parent relationships on adolescent mental health during lockdown in the UK. Young people aged 11–16 years (n = 894) completed measures of loneliness, social contact, parent-adolescent relationships, and mental health difficulties during the first 11 weeks of lockdown and one-month later (n = 443). We examined cross-sectional associations and longitudinal relationships between loneliness, social contact, and parent relationships and subsequent mental health. Adolescents who reported higher loneliness had significantly higher symptoms of mental health difficulties during lockdown. We found that adolescents who had closer relationships with their parents reported significantly less severe symptoms of mental health difficulties and lower levels of loneliness. We also found that adolescents who spent more time texting others reported higher symptoms of mental health difficulties. Our hypothesis that loneliness would predict poorer mental health one month later was not supported. Time spent texting others at baseline was significantly associated with higher hyperactivity at follow-up, and closeness to parents was significantly associated with lower psychological distress at follow-up. We conclude that while loneliness was associated with greater mental health difficulties at baseline, it did not predict increased mental health difficulties one month later. Moreover, existing mental health problems significantly predicted later increase, thereby highlighting the importance of continuing support for vulnerable people.